2016
DOI: 10.1136/neurintsurg-2015-012240
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion of bifurcation aneurysms is more effective when the jailed branch is occluded: an experimental study in a novel canine model

Abstract: Treatment failures following flow diversion of bifurcation aneurysms can be caused by persistent flow to the jailed branch. Branch occlusion combined with flow diversion may improve angiographic occlusion scores of a canine bifurcation aneurysm model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…One explanation of the lower occlusion rate observed with flow diversion for bifurcation aneurysms might be the persistent flow through the covered braches incorporated by the aneurysm. Fahed et al ( 47 ) compared flow diversion with and without occlusion of the jailed branch in 14 wide-neck aneurysms induced in 8 canines and found that occlusion of the jailed branch resulted in better occlusion rates of aneurysmal occlusion. Patent aneurysms were associated with leaks or holes in the neo-intima covering the aneurysm neck.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation of the lower occlusion rate observed with flow diversion for bifurcation aneurysms might be the persistent flow through the covered braches incorporated by the aneurysm. Fahed et al ( 47 ) compared flow diversion with and without occlusion of the jailed branch in 14 wide-neck aneurysms induced in 8 canines and found that occlusion of the jailed branch resulted in better occlusion rates of aneurysmal occlusion. Patent aneurysms were associated with leaks or holes in the neo-intima covering the aneurysm neck.…”
Section: Discussionmentioning
confidence: 99%
“…The occlusion of aneurysms at branch points has also been investigated. Fahed et al 41 compared flow diversion with and without occlusion of the jailed branch in 14 wide neck aneurysms induced in 8 canines. They found that occlusion of the jailed branch resulted in better occlusion rates of aneurysmal occlusion whereas patent aneurysms were associated with less dense neointimal coverage and persistent holes in the neointima.…”
Section: Discussionmentioning
confidence: 99%
“…29 More complex aneurysm models have been constructed in canines. 5,[29][30][31] Some models were so challenging that aneurysms remained patent despite implantation of multiple flow diverters. 31,32 The complex fusiform aneurysms created in this work were larger than the standard rabbit elastase carotid model, but they remain of modest size compared with most canine vein pouch aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…2 A number of experimental aneurysm models are available to test neurovascular devices. [3][4][5] The most commonly used model is the rabbit elastase-induced saccular aneurysm model. [6][7][8][9] The model can be created by using endovascular techniques with low morbidity.…”
mentioning
confidence: 99%